Reliable addition of reagents into microfluidic droplets - Sivasamy Jayaprakash (2012)
This article reports a design that reliably adds reagents into droplets by exploiting the physics of fluid flow at a T-junction in the microchannel. An expanded section right after the T-junction enhances merging of a stream with a droplet, eliminates the drawbacks such as extra droplet formation and long mixing time. The expanded section reduces the pressure buildup at the T-junction and minimizes the tendency to form extra droplets; plays the role in creating low Laplace pressure jump across the interface of the droplet forming from the T-junction which reduces the probability of forming extra droplet in the merging process; provides space for droplet coalescence if there is an extra droplet due to droplet break-up before merging. In this design, after merging, the reactants are in axial arrangement inside the droplets which lead to faster mixing. Reliable addition of reagent to the droplets happens for the combination of flow rates in a broad range from 25 to 250 μl/h, for both DI water (Q DI) and fluorescent (Q fluo) streams.